The safety of nonsteroidal anti-inflammatory drugs in population-based studies: the benefits of aceclofenac - E. Yu. Pogozheva (Современная ревматология, 2020)
Effective pain relief in rheumatology practice is one of the most important criteria for the quality of medical care. Therefore, drugs with analgesic effects, primarily nonsteroidal anti-inflammatory drugs (NSAIDs), are among the most commonly used ones in the combination therapy of rheumatic diseases. All NSAIDs are capable of causing to one degree or another extent unwanted reactions that occur in the gastrointestinal tract (GIT), cardiovascular system (CVS), liver, kidneys, and allergic reactions. Considering the widespread use of NSAIDs, the problem of preventing these complications becomes not only medical, but also social. In 2008, the European Union launched the international project SOS (Safety Of non-Steroidal anti-inflammatory drugs) to study the safety of NSAIDs. The results of this project have shown that aceclofenac is one of the most successful drugs in combining the safety for GIT and CVS. Compared with other NSAIDs, this drug has a minimal risk for GI bleeding (relative risk (RR) 1.43; 95% confidence interval (CI), 0.65–3.15); it does not increase the risk of hospitalization for heart failure (RR, 1.03; 95% CI, 0.91–1.15) or the risk of developing myocardial infarction (RR 1.04; 95% CI, 0.90–1.19) either. The risk of ischemic stroke during aceclofenac therapy was slightly increased (RR, 1.17); but statistically insignificant (95% CI, 0.98–1.39). A large number of randomized clinical trials, meta-analyses, and observational programs have demonstrated that aceclofenac has pronounced analgesic and anti-inflammatory effects that are comparable to those of other NSAIDs and can be used in diseases accompanied by musculoskeletal pain, including that in older patients.